Perceptions of People with Intellectual Disabilities and Their Families Regarding Sexual and Reproductive Rights in the Social Inclusion Programs of AVANZA Inclusión. (Palimpsesto, 2025)
This qualitative research analyzes the perceptions of people with intellectual disabilities and their families regarding the sexual and reproductive rights workshops conducted within AVANZA Inclusión's programs. Through virtual focus groups, the study identifies meanings, learnings, and cultural barriers that affect the exercise of these rights. The role of these spaces is discussed as tools to promote self-determination, consent, and social inclusion from a rights-based approach. The findings reveal knowledge about consent, contraception, abuse prevention, and reproductive decision-making.
Keywords: Intellectual disability, sexuality, rights, workshops, autonomy.